2021
DOI: 10.1259/bjr.20211018
|View full text |Cite
|
Sign up to set email alerts
|

PET/MR in recurrent glioblastoma patients treated with regorafenib: [18F]FET and DWI-ADC for response assessment and survival prediction

Abstract: Objective: The use of regorafenib in recurrent glioblastoma patients has been recently approved by the Italian Medicines Agency (AIFA) and added to the National Comprehensive Cancer Network (NCCN) 2020 guidelines as a preferred regimen. Given its complex effects at the molecular level, the most appropriate imaging tools to assess early response to treatment is still a matter of debate. Diffusion-weighted imaging and O-(2-18F-fluoroethyl)-L-tyrosine positron emission tomography ([18F]FET PET) are promising meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 46 publications
1
9
0
Order By: Relevance
“…MR images have been used more frequently to predict survival in a radiomics-based approach. The performance reported in our study based on 18 F-FET PET images are in line with previously reported outcomes on MRI-based radiomics in glioblastoma [ 33 38 ]. These studies include also more recent extensions from traditional radiomics to deep learning models, designed to include traditional risk factors as potential predictors [ 35 ].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…MR images have been used more frequently to predict survival in a radiomics-based approach. The performance reported in our study based on 18 F-FET PET images are in line with previously reported outcomes on MRI-based radiomics in glioblastoma [ 33 38 ]. These studies include also more recent extensions from traditional radiomics to deep learning models, designed to include traditional risk factors as potential predictors [ 35 ].…”
Section: Discussionsupporting
confidence: 91%
“…Therefore, 18 F-FET PET images are suggested as valuable candidates for the prediction of overall survival in primary glioblastoma patients. The complimentary use of MRI and 18 F-FET PET images has been recently shown in recurrent glioblastoma patients to derive independent biomarkers of response to treatment [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Again, regorafenib proved to have an effectiveness comparable to that of REGOMA, with an even longer survival time [ 10 ]. Although clinical data are accumulating, demonstrating encouraging efficacy and tolerability of regorafenib in GBM patients [ 10 , 11 , 15 , 46 ], the mechanisms governing GBM response to regorafenib have been poorly investigated. Santangelo and colleagues [ 12 ] identified five biomarkers which could help in identifying a subpopulation of GBM patients exhibiting a striking survival advantage when treated with regorafenib.…”
Section: Discussionmentioning
confidence: 99%
“…In patients with recurrent HGGs treated with regorafenib (multikinase inhibitor), FET and DWI-ADC metrics can predict the overall survival, and could serve as semiquantitative independent biomarkers of response to treatment. 46 A recent study analyzed data from patients with GBM who received autologous dendritic cell vaccination therapy. In MR imaging for suspicion for GBM recurrence, FET-PET showed congruent tumor progression in 3/5 patients and TRC in the remaining 2/5.…”
Section: Monitoring Treatment Response To Newer Drugs In Recurrent Hg...mentioning
confidence: 99%